SWI/SNF chromatin remodelers in prostate cancer progression - Ordonez-Rubiano, Sandra C.; Strohmier, Brayden P.; Sood, Surbhi; Dykhuizen, Emily C. (Frontiers in Epigenetics and Epigenomics, 2024)
Prostate cancer (PCa) is the most commonly diagnosed cancer and the second most common cause of cancer-related deaths in men in the US. The majority of PCa cases arise in the luminal cells of the prostate and develop into adenocarcinoma. Primary PCas are heterogeneous and have alterations in a variety of tumor suppressors and oncogenes; however, the vast majority are dependent on gene expression regulation by androgen receptor (AR), making it the focus for most targeted therapy development. As the incidence of PCa cases resistant to AR-targeted therapies rises, there is renewed attention on how additional genetic and epigenetic alterations contribute to PCa progression and resistance. In this review we summarize the efforts made over the past 20 years to dissect the function of the SWI/SNF chromatin remodelers in PCa. We mainly focus on how SWI/SNF complexes regulate different aspects of AR signaling, facilitate other key drivers in PCa, promote the advancement of the disease, and regulate the tumor microenvironment.